2016
DOI: 10.25115/psye.v8i2.455
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficacia de profesores de educación física para la inclusión de alumnos con discapacidad y su relación con la formación y el contacto previo

Abstract: RESUMEN:La formación y experiencias positivas previas son fundamentales para una adecuada percepción de competencia, confianza y actitud positiva para la inclusión de alumnos con discapacidad en educación física. Este trabajo analiza la fiabilidad de una escala aplicada al contexto español para evaluar las creencias de autoeficacia para atender a alumnos con discapacidad intelectual, física y visual, mostrando excelentes valores de fiabilidad y consistencia interna la Escala de Autoeficacia en Profesores de Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 34 publications
(48 reference statements)
1
12
1
13
Order By: Relevance
“…The results for Cronbach's reliability analysis of the SE-ASPE reached very high scores (α for the ID subscale =0.96, α for the PD subscale =0.97, α for the VI subscale =0.98) and were comparable Cronbach's α values obtained in previous surveys conducted in the USA, ranging 0.86 -0.96 (Block et al 2013;Taliaferro et al 2015), and to those reported by Reina et al (2016) in a fairly similar sample of 102 practicipng teachers (59.8% males) with a mean experience of 14.87+ 9.02 years (α = 0.975 for the PD subscale and 0.935 for both the ID and VI subscales). These outcomes appear to present a similar hrather than a different response pattern of the Arabic-speaking PE teachers to American and European samples.…”
Section: Attitudes and Self-efficacy Scales' Structuresupporting
confidence: 73%
See 1 more Smart Citation
“…The results for Cronbach's reliability analysis of the SE-ASPE reached very high scores (α for the ID subscale =0.96, α for the PD subscale =0.97, α for the VI subscale =0.98) and were comparable Cronbach's α values obtained in previous surveys conducted in the USA, ranging 0.86 -0.96 (Block et al 2013;Taliaferro et al 2015), and to those reported by Reina et al (2016) in a fairly similar sample of 102 practicipng teachers (59.8% males) with a mean experience of 14.87+ 9.02 years (α = 0.975 for the PD subscale and 0.935 for both the ID and VI subscales). These outcomes appear to present a similar hrather than a different response pattern of the Arabic-speaking PE teachers to American and European samples.…”
Section: Attitudes and Self-efficacy Scales' Structuresupporting
confidence: 73%
“…These associations were stronger than those reported in previous studies, particularly the recent Spanish study of Reina et al (2016) that reported moderate r scores (between 0.575 -0.648). This finding indicates that teachers who reported high SE toward one disability also reported high SE scores toward the inclusion of children with different types of disability.…”
Section: Impact Of Disability Typecontrasting
confidence: 55%
“…The Self-Efficacy Scale for Physical Education Teacher Education Majors towards Children with Disabilities (SE-PETE-D) was used to evaluate changes in SE. The questionnaire was created and validated by Block et al [17] in English and adapted to the Spanish context by Reina, Hemmelmayr, and Sierra-Marroquín [18] (Escala de Autoeficacia en Profesores de Educación Física hacia Alumnos con Discapacidad (EA-PEF-AD)). The questionnaire begins with a general introduction to Bandura's SE theory and general guidance for using the rating scale to answer the questions.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the Spanish context, approximations have been made. On the one hand, Reina et al (2016) reported excellent reliability values for the SE-PETE-D in a sample of 102 in-service PE Teachers. On the other hand, Abellán et al (2019) using the version of Reina et al (2016) in a sample of 228 university students of Childhood and Primary Education Degrees who studied the PE specialty, obtained values below the recommended ones for three fit indexes when testing the factorial and invariance structure of the scale, although it obtained acceptable reliability.…”
Section: Introductionmentioning
confidence: 96%
“…However, many of these works were applied with non-active in-training teachers (e.g., Taliaferro et al, 2015; Kudlaček et al, 2018; Abellán et al, 2019), so little is known about its reliability in day-to-day PE. In addition, previous studies have not provided evidence of its psychometric properties or reliability (e.g., Jovanović et al, 2014; Tekidou et al, 2015; Reina et al, 2016; Tindall et al, 2016) despite its application in countries with disparate demographic, cultural, and linguistic characteristics. In terms of the Spanish context, approximations have been made.…”
Section: Introductionmentioning
confidence: 98%